Evaluation of Microbiological Indicator Contamination (Escherichia coli) and Heavy Metal Levels in Edible Fish from Situ Bambon, Ciracas: A Health Risk Assessment - Haerul Anwar; Nadirahillah; Faisal M Jasin; Bayu Achil Sadjab; Cornelia Victoria Anghel; Amir Machmud (International Journal of Hydrological and Environmental for Sustainability, 2026)
Situ Bambon in Ciracas, East Jakarta, is utilized by the local community for daily activities ranging from recreation, angling, to net fishing. The community frequently utilizes the areas around the inlet, midstream, and outlet to catch fish. This study aims to evaluate the content of the microbiological indicator E. coli and heavy metal levels in edible fish from Situ Bambon Ciracas to obtain a comprehensive Health Risk Assessment. The results showed that the microbiological contamination levels through the Escherichia coli indicator in edible fish ranged from <1.8 to 13.9 MPN/g, indicating that fish samples in the inlet 1 and outlet 2 areas failed to meet food safety standards (< 3 APM/g). The worst concentrations of Cadmium (Cd) and Lead (Pb) in edible fish from Situ Bambon were found in the inlet 2 area, with a Cd value of 0.83 mg/kg and a Pb value of 0.80 mg/kg. The obtained Cd and Pb contamination levels exceeded the Maximum Contaminant Limits (MCL) established by PerBPOM Number 9 of 2022, where Cd was approximately 8.3 times higher, while Pb exceeded the limit by about 2.7 times. The Health Risk Assessment (HRA) indicated that the Hazard Index (HI) value of 1.489 exceeded the allowable tolerance threshold of 1.0. Risk contribution analysis showed that Cd accounted for 51.0% of the total HI risk, while Hg contributed 35.0%. Furthermore, the carcinogenic risk (cancer) was evaluated through the Total Risk (TR) for Cadmium (Cd) because it possesses the highest Slope Factor (SF) of 0.38 (mg/kg-day)⁻¹, calculated based on the Lifetime Average Daily Dose (LADD) and SF, yielding a result of 3.37 x 10⁻⁷. This value remains below the internationally acceptable carcinogenic risk threshold of TR < 10⁻⁶. The environment-fish-human exposure cycle in Situ Bambon has reached a hazardous threshold and demands top-priority intervention to protect public health.